DIGITAL TOURISM MUSEUM NASIONAL INDONESIA MELALUI VIRTUAL TOUR DI MASA PANDEMI COVID-19 - Bagus Dwi Bramantyo; Pitoyo Ismail (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2021)
The Covid-19 pandemic that has hit Indonesia has succeeded in forming new adaptations of people's habits, one of which is social distancing. The government has appealed to the public to carry out activities from home. Museum Nasional Indonesia as a tourist destination was also affected because it had to close direct visit services. However, Museum Nasional Indonesia provides innovation by utilizing digital tourism, namely through virtual museum tours. Later, the public can visit the Museum Nasional Indonesia virtually. The purpose of this study is to find out Digital Tourism at Museum Nasional Indonesia through Virtual Tours during the Covid-19 Pandemic Period. This research uses a case study method with a qualitative approach and constructivism paradigm. This research uses diffusion of innovation theory from Everett M. Rogers, which explains how to introduce and adapt an innovation by a community or group to society. The results of this study indicate that virtual museum tours are a way for Museum Nasional Indonesia to continue to reach and provide museum services to the public, of course, so that they remain interested and can visit museums during the Covid-19 pandemic.